Drilidae Blanchard, 1845: multi-gene molecular phylogenies versus morphological similarity. An answer to Kovalev et al. - Bocak, Ladislav; Kusy, Dominik; Motyka, Michal; Bocek, Matej (Zootaxa, 2019)
In a recent issue of Zootaxa, Kovalev et al. (2019) reported the description of a new drilid genus Drilorhinus Kovalev, Kirejtshuk et Shapovalov, 2019 and they discuss at length the relationships and systematic classification of the drilid lineage. Although they did not formally propose a new status for Drilidae Blanchard, 1845 [not Lacordaire, 1857, as cited in their study] in the sense of the Code (ICZN 1999), they in fact resurrected the traditional concept of Drilidae as a separate ‘cantharoid’ family and rejected Drilini in Elateridae: Agrypninae of Kundrata & Bocak (2011). The authors strongly defended the historical classification of the genera Selasia Laporte, 1838, Malacogaster Bassi, 1834, Drilus Olivier, 1790, Drilorhinus, and putatively also their relatives (Kundrata et al. 2017), as a separate ‘cantharoid’ family in the sense proposed in 19th century and held until recently by some traditional morphologists (Blanchard 1845; Crowson 1955, 1972; Lawrence & Newton 1982, 1995; Branham & Wenzel 2003; Lawrence et al. 2011; Kazantsev 2013; Lawrence & Ślipiński 2013; Lawrence 2016). Although no new data were presented or methodological flaws of earlier analyses identified by Kovalev et al., the authors argued that the present evidence is insufficient for the placement of the Drilini in Elateridae, Agrypninae. Unfortunately, they did not take into account recent molecular analyses suggesting multiple origins of soft-bodied elateroid families, i.e., the polyphyly of the historical cantharoid group of families, and the relationships of drilids and agrypnine click beetles (Bocakova et al. 2007; Hunt et al., 2007; Timmermans et al. 2010, 2016; Kundrata et al. 2014; McKenna et al. 2015; Bocak et al. 2016; Kusy et al. 2018a, b; Linard et al. 2018; Zhang et al. 2018). They only discussed a single molecular analysis by Kundrata & Bocak (2011).